A numerical study of neutrally buoyant slickwater proppant flow and transport in rough fractures. (March 2022) - Yamashiro, Brian D.; Tomac, Ingrid
Abstract: Influence of rough rock surface geometry on flow behavior for single and multiple neutrally buoyant particles in fractures is explored. Degree of roughness is evaluated by varying synthetic surfaces' root-mean-square asperity height and fractal dimension. Influences of flow Reynolds number and multiparticle volumetric concentration are also considered. Simulated behavior of particles within fluid is performed utilizing resolved computational fluid dynamics with the Discrete Element Method. Behavior within rough fracture apertures is contrasted against behavior within smooth wall fractures. Findings show accentuation in particle transport rate for some rough fractures at intermediate particle diameter to mechanical aperture ratio values. Further narrowing of fracture mechanical aperture past these intermediate values leads to increased particle–wall collision interactions, causing attenuation of particle transport rate and eventual particle arrest. Mechanical aperture in rough fractures where particle arrest occurs is appreciably larger than particle diameter and largely depend on surface fractal dimension and asperity height root-mean-square. Multiparticle flow and transport evaluations also reveal that increased particle interactions lead to varied hydraulic aperture values. Hydraulic aperture is found to be dependent on combined effects from injection particle volumetric concentration and surface roughness at moderate mechanical aperture, with increasing importance of surface roughness as mechanical aperture narrows. Further, it is found that particle jamming depends more on fracture geometry than injected particle volumetric concentration. This work provides a unique micro-level perspective of particle slurry behavior within rough rock fracture interfaces, pointing to the shortcomings of assumed analogous smooth-walled fracture face behavioral characterizations utilized in past investigations. Highlights: Volumetric concentration minimally impacts jamming compared to roughness. Proppant conveyance can attenuate or intensify depending on roughness and aperture. Particle arrest in rough fractures is highly dependent on roughness parameters. Surface roughness and particle concentration have a combined effect on transport. Hydraulic aperture influenced by combined roughness and concentration effects.